The Use of Instagram in the Halal Food Information Sharing among Virtual Communities - Naumi, Adinda Tessa; Sumardjo; Amanah, Siti; Hapsari, Dwi Retno (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Virtual communities refer to people who use and share information on social media through the Internet. A virtual community that cares about the Halal lifestyle creates and shares content widely using Instagram to raise people’s awareness of halal food. This article explores the use of Instagram in sharing information on halal food. This article is qualitative in nature and applies Virtual ethnography. The research subjects are the Halal Corner team and followers. The data is collected through observation, interview, and documentation. They are analyzed using the virtual ethnography method by Boellstorff. This article finds numerous reasons to share information on halal food through Halal Corner Instagram. The reasons are effective communication, social connectedness, content production, content characteristics and features, and reliable information source.